PENGARUH KUALITAS PRODUK, VARIASI PRODUK, KESESUAIAN HARGA, CITRA MEREK DAN KESADARAN MEREK DALAM UPAYA MENINGKATKAN KEPUTUSAN PEMBELIAN (STUDI KASUS PADA STRADA COFFEE SEMARANG) - Sulistyorini, Oktavia Dyah; Rahardjo, Susilo Toto (Diponegoro Journal of Management, 2018)
Strada coffee has decreased sales in 2016-2017. one of the factors influencing the decrease of sales is the competition of coffee shop in Semarang which is very tight so as to make the level of customer decrease and cause the sales decrease.This research is used to analyze the effect of product quality, product variation, price appropriateness, brand image and brand awareness in an effort to improve purchasing decision of Strada Coffee Semarang. Strada Coffee is a coffee shop that provides  a  variety of  coffee products  such as  beverages  and  coffee beans  have been established since 2012 by Evani Jesslyn. The development of the business world in Indonesia increasingly rapidly and cause a more intense competition especially in the coffee shop business. This is seen in 2017 and Strada Coffee sales decreased.Sampling  technique  used  in  this  research  is  convenience  sampling  that  is sampling based on convenience. The researcher has no other considerations except based on convenience. Respondents in this study are Strada Coffee consumers who have visited the coffee shop at least 2 times, with the number of respondents 100 people.The results of research show that from the five independent variables in this study have a positive influence on the dependent variable that is the purchase decision. The coefficient of determination test results stated that the five independent variables have an effect of 86.1% of the Purchase decision. Strada Coffee as a coffee shop is recommended to build a good brand image by providing quality products and product variations so that consumers will be aware of the brand, it can improve purchasing decisions.